Mixed race life stories : the multiracializing gaze in Canada - Paragg, Jillian (Critical mixed race studies., 2023)
Framing a new theoretical analysis in a field with limited data, Mixed Race Life Stories: The Multiracializing Gaze in Canada builds an understanding of the affective lived experiences of mixed race people, the different ways they are racialized and how that may impact a politics of mixed race moving forward.